An Electrochemical and Computational Analysis of Electronic Communication in a "Molecular Spider". Issue 13 (5th May 2017) - Mohammad, M.; Rauf, A.; Rauf, S.
Abstract: A reversible "3S" ‐ sharing, spreading and storing ‐ information strategy has been proposed which explains electronic communication at molecular level. Cyclic voltammetric and computational response reveal that disaccharide sucrose molecule coupled with tetrachlorobenzoquinone dianion (TCBQ 2− ) forms weak donor ‐ acceptor hydrogen bonded complex. DFT studies feature this redox couple to a unique geometry – a spider like molecule. This molecular spider switches, ON/OFF via redox response by 3S strategy. Electronegative atoms (such as "oxygen") are supposed to be more prone to electronic communication process. The extent as well as rate of molecular communication could be estimated by stability constant (Ka ) and rate constant (km ). The values of Ka and km were found to be 7.5×10 4 M −m and 1.33(±1.0)×10 8 M −m . s −1 (1.2(±1.0) ×10 6 M −m . s −1 ) respectively. Abstract : A reversible "3S" ‐ sharing, spreading and storing ‐ information strategy has been proposed which explains electronic communication at molecular level. Cyclic voltammetry reveals that disaccharide sucrose molecule coupled with tetrachlorobenzoquinone dianion (TCBQ 2− ) forms weak donor ‐ acceptor hydrogen bonded complex. DFT study features this redox couple to a unique geometry – a spider like molecule. The extent and rate of molecular communication between TCBQ 2− and sucrose were estimated to 7.5×10 4 M −m and 1.2(±1.0)×10 6 M −m . s −1 respectively.